PHILOSOPHY ART THERAPY 1 (PATH 1 SPECIAL EDITION, 2022)
Philosophy, Arts, Therapies: PATh! A path toward a human protective life through Philosophy, Arts and Therapies! An innovative, interdisciplinary and humanistic approach for a life with meaning and freedom. Every paper opens a new path for self-awareness, meaningful communication with significant others, solidarity and creativity as the healthiest approach to human growth. Philosophy as well as the arts contains the potential for humans to exceed the limits of physical existence and transcend self so that man rises above mundane needs to reach elevation. It is when emotional and spiritual transcendence occurs through the innate healing qualities of philosophy and arts that man can become a man. Moreover, the fathers of psychoanalysis, humanistic and existential psychotherapies, i.e. Sigmund Freud, Carl Jung, Jacques Lacan, to mention a few, supported their theories and practice through philosophical currents and some of them, i.e. Carl Jung, Rollo May etc., derived profound inspiration from the arts.